Biomed Europa: After the coronavirus, a public infrastructure to overcome the pharmaceutical oligopoly. (23rd July 2021) - Florio, Massimo; Gamba, Simona
Abstract: After a brief analysis of the causes underlying the failure of both governments and the pharma industry in terms of preparedness for the COVID‐19 pandemic, and after a discussion of further risks of health emergencies in the coming decades, this paper proposes a new public policy approach. The proposal aims at a major European initiative for the provision of research and development (R&D) in the biomedical field, based on public health priorities. A plan is discussed for an international, interconnected, transparent, science‐informed and publicly funded research infrastructure for pharmaceutical and biomedical research combined with a public enterprise: Biomed Europa. The proposed platform aims to identify research priorities in the public health sector, focusing its efforts on the development of preventive and therapeutic strategies against those diseases that will pose the greatest threats to human and social welfare over future decades. Biomed Europa could be managed as both an international research infrastructure, along the model of CERN, or the EMBL (European Molecular Biology Laboratory, Heidelberg) and as a knowledge‐intensive public enterprise with an industrial policy mission, such as the ESA (European Space Agency).